Formulation and pH-Physical Stability Evaluation of Gel and Cream of Plantago major Leaves Extract - Kartini Kartini; Babtista Merchyta Winarjo; Endang Wahyu Fitriani; Ridho Islamie (MPI (Media Pharmaceutica Indonesiana), 2017)
Plantago major has been widely used for wound healing. This activity is supported by empiricalas well as preclinical data. The aims of this study were to (1) formulate Plantago major leaves extracts(PMLE) into topical dosage forms i.e. creams and gels and; (2) evaluate the pH and physical stability of theproducts. The results showed that creams and gels of PMLE were able to maintain the pH, visual appearance,flow properties, droplet size, and type of emulsion under accelerated (40±2 °C; 75±5% RH for 1.5 months)as well as room temperature (27 °C; 85% RH for 1.5 months) stability testing conditions. However, viscosityof creams significantly changed under those conditions. Even though the viscosity of gels was unstableunder accelerated condition, it was stable under room temperature storage. It is concluded that PMLEcould be formulated into creams or gels dosage forms and further optimisation should be conducted.